UNVEILING GENDER BIAS IN LEARNING MATERIALS: A MULTIMODAL STUDY OF MALE AND FEMALE REPRESENTATIONS ININDONESIAN PRIMARY ELT TEXTBOOKS - Andriani, Agis; Rahayu, Kristia Maulida; Sri, Melisa (ppjbsip, 2026)
This study investigates gender representation in the My Next Words English textbook for Grade 3, developed under Indonesia’s Emancipated Curriculum. Using the Systemic-Functional Multimodal Discourse Analysis (SF-MDA) framework, which integrates Halliday’s transitivity system and Kress & van Leeuwen’s visual grammar, the research analyzes textual and visual elements from two selected units. The findings reveal consistent patterns of imbalance in gender representation. Male characters are frequently positioned as active participants through material processes, central placement in illustrations, and visual prominence achieved through size, color, and composition. In contrast, female characters are often depicted in passive or symbolic roles, associated with social or cultural identity markers such as the hijab, and placed in supporting positions within the visual layout. While these portrayals reflect broader cultural norms, they also risk reinforcing traditional gender stereotypes among young learners. The study highlights that such patterns are not neutral but ideological, shaping students’ perceptions of gender roles from an early age. These findings suggest the need for greater attention to gender equity in the design of educational materials. The paper recommends that curriculum developers, textbook writers, and teachers critically evaluate gendered representations to foster more inclusive learning environments. Future research should expand to multiple grade levels and publishers and explore students’ and teachers’ responses to these materials to provide a more comprehensive understanding of how textbooks construct gender identities in education.